(untitled) (Journal of Partial Differential Equations, 1990)
In this note we consider the first boundary value problem for a general parabolic Monge-Ampere equation u_t - log det(D_iju) = f(x, t, u,D_2u) in Q, u = &#966(x, t) on &#8706, Q It is proved that there exists a unique convex in x solution to the problem from C^1+&#946,2+&#946/2(Q) under certain structure aod smoothness conditions (H3) - (H7).